Validitas dan Reabilitas Instrumen Korelasi Antara Intensitas Membaca Al-Qur’an dan Sikap Religius Mahasiswa - Djuned, Muslim; Nurmayuli, Nurmayuli; Maghfirah, Annisah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Research on the correlation between the intensity of reading the Qur'an and the religious attitude of students requires valid and reliable instruments to measure these two variables. Instrument validity and reliability are important aspects in ensuring the validity of the data obtained. This study aims to prove the validity and reliability of the instrument correlating the intensity of reading the Qur'an and the religious attitude of students. This research uses quantitative methods. The population in this study consisted of students of the Al-Qur'an Science and Tafsir Study Program of UIN Ar-Raniry with a sample size of 30 students selected by simple random sampling. The results of the study prove that the instrument of the correlation of the intensity of reading the Qur'an and the religious attitude of students has sufficient validity and reliability to be used in measuring the correlation of the intensity of reading the Qur'an and the religious attitude of students.